2015
DOI: 10.1371/journal.pone.0138944
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Admission following Acute Kidney Injury in Kidney Transplant Recipients Is Associated with a Negative Impact on Graft Function after 1-Year

Abstract: The incidence and outcomes of acute kidney injury (AKI) in kidney transplantation are poorly known. Retrospective cohort analysis was performed on the data of all patients (≥3 months after transplantation and ≥16 years of age) admitted to the hospital due to medical or surgical complications from 2007 to 2010. We analyzed 458 kidney transplant recipients, 55.2% men, median age 49 (IQR, 36–58) years, median of 12.5 (IQR, 3–35) months after kidney transplantation; admitted to the hospital due to medical or surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
3
19
1
Order By: Relevance
“…Filiponi et al. 8 recently shown the incidence as 80% from 458 hospitalized transplant recipients and defined the AKI by AKIN criteria. Nakamura et al.…”
Section: Discussionmentioning
confidence: 99%
“…Filiponi et al. 8 recently shown the incidence as 80% from 458 hospitalized transplant recipients and defined the AKI by AKIN criteria. Nakamura et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplant recipients are susceptible to AKI, due to the presence of only one kidney and lack of kidney reserve, susceptibility to infections due to immunosuppression, immunologic vulnerability of the graft, and the use of nephrotoxic drugs. Filiponi et al reported an 82.3% incidence of AKI, as defined by the KDIGO criteria, in kidney transplant recipients admitted to the hospital more than 3 months after transplantation. In another study, Mehrotra et al reported an incidence of AKI, as defined by the ICD‐9CM codes, of 11.3%, in kidney transplant recipients admitted to the hospital more than 6 months after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort, AKI was highly prevalent (81.5%) and 51.5% of patients required RRT, contrasting with unselected critically ill patients (19 to 57% and 4.5 to 13.5%, respectively) [30, 31]. In addition to known risk factors for the development of AKI in the ICU, the use of calcineurin inhibitors, the previous episodes of AKI and the underlying CKD, all increased the risk of AKI in KTR with acute condition [13, 14, 32, 33]. Moreover, we showed that progression of CKD after admission to the ICU is highly prevalent (30% at 1 month and 45% at 6 months in our series, compared to 12–20% at 3 months in older studies [3, 4, 11] and was well predicted by the basal CKD stage and the severity of the AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to unselected critically ill patients, renal outcome of KTR results from the combination of the underlying CKD ( i.e , basal eGFR), the use of nephrotoxicants in the ICU, and episodes of ischemic, hemodynamic or septic AKI [3, 4, 14]. In the setting of renal transplantation, immunological injuries may also promote the progression of graft dysfunction observed after ICU admission.…”
Section: Introductionmentioning
confidence: 99%